Representations of non-suicidal self-injury in motion pictures - Trewavas, C.; Hasking, Penelope; McAllister, M. (Routledge, 2010)
The aim of this study was to investigate representations of non-suicidal self-injury (NSSI) in popular media. Forty-one motion pictures were viewed, coded, and analyzed. NSSI was correlated with mental illness, child maltreatment, and substance abuse. NSSI was generally portrayed as severe, habitual and covert. Further, depictions of NSSI were often sensationalized and featured prominently. NSSI was less likely to be associated with completed suicide than other psychological factors, but more closely associated with suicide than NSSI is in the community. Although NSSI was associated with psychiatric illness, few characters were receiving psychiatric care at the time of NSSI. However a significant proportion received support after engaging in NSSI. The portrayal of NSSI is generally accurate regarding correlates and function, but is inaccurately associated with suicide. Implications of the relatively accurate portrayal of NSSI are discussed in light of the potential for imitation, and the possibility of using cinematherapy to promote effective problem resolution.